Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/0884533617700862
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip Strength Is Associated With Treatment Modifications During Neoadjuvant Chemoradiation in Patients With Esophageal Cancer

Abstract: Rationale: It has been shown that early nutrition intervention improves nutrition status (NS) and treatment tolerance in patients with esophageal cancer. However, it remains unknown whether pretreatment parameters of NS are associated with treatment modifications (TMs) during neoadjuvant chemoradiation (CR) in patients who are intensively nutritionally supervised during treatment. Methods:All outpatients with esophageal cancer who were scheduled for CR in the VU medical center from 2006–2015 were included. NS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
(59 reference statements)
2
8
0
Order By: Relevance
“…Although significance disappeared in multivariable analyses, low handgrip strength also seemed to be associated with poorer tolerance of cCHRT. This is in line with previous studies which have shown an association between low handgrip strength before treatment and an increased risk of poor treatment tolerance in patients with oesophageal and colorectal cancer [36][37][38]. Results of the current study and previous studies therefore suggest that BMI < 18.5 kg/m 2 , poor WHO performance status and low handgrip strength before treatment might have an added value in identifying patients at high risk of poor tolerance of cCHRT.…”
Section: Discussionsupporting
confidence: 92%
“…Although significance disappeared in multivariable analyses, low handgrip strength also seemed to be associated with poorer tolerance of cCHRT. This is in line with previous studies which have shown an association between low handgrip strength before treatment and an increased risk of poor treatment tolerance in patients with oesophageal and colorectal cancer [36][37][38]. Results of the current study and previous studies therefore suggest that BMI < 18.5 kg/m 2 , poor WHO performance status and low handgrip strength before treatment might have an added value in identifying patients at high risk of poor tolerance of cCHRT.…”
Section: Discussionsupporting
confidence: 92%
“…Although the main outcome of the study was not to evaluate the effects of the intervention on nutritional status and body composition, this finding corroborates the positive results of the nutritional intervention on role function evaluated as an aspect of QoL. A previous study showed that the strength of the upper limbs in women diagnosed with breast cancer is reduced [ 36 ] and this highlights the importance of measuring the HGS in this public, which can correlate with the loss of muscle mass [ 37 ] as well as being associated with musculoskeletal symptoms [ 38 , 39 ], reduced physical function [ 38 , 40 ], increased occurrence of adverse events [ 39 ] and/or complications during treatment [ 41 ], therapy change [ 42 ] and higher mortality [ 43 , 44 ] for various types of cancer. The relationship between the preservation of muscle strength and QoL is indisputable, demonstrating another benefit of adequate nutrition as a positive agent for maintaining nutritional status and, consequently, physical function.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques including the use of handgrip strength (HGS) have been shown to be a functional measure of muscle mass [8] and may be a simple, cost-effective measurement to complete in an outpatient setting [9]. Low handgrip strength is associated with increased mortality in a mixed cohort of cancer diagnoses [10,11], treatment modification (such as delay in chemo/radiotherapy >1 week, dose reduction, hospital admission or discontinuation of treatment) during chemoradiotherapy in oesophageal cancer [12] and as a predictor of postoperative complications in adults following oesophagectomy [13e15].…”
Section: Introductionmentioning
confidence: 99%